(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2024)
The importance of leadership within organizations is essential, over time leadership will have an impact on the performance of the members of an organization or work team by providing guidance to achieve the objectives and goals of the organization, we refer to those goals. that any body, whether called a company or business, is interested in fulfilling, since it allows it to adapt to any dynamic business environment, motivating, inspiring, and achieving the established objectives to ensure sustainable growth and profitability, while innovation, meeting goals and leadership. They are key parts for an organization to achieve clear and precise objectives for the success and survival of a company and achieve a boost for an organizational culture focused on achieving results.